Protein Allostery and Ligand Design: Computational Design Meets Experiments to Discover Novel Chemical Probes. Issue 17 (15th September 2022) - Triveri, Alice; Sanchez-Martin, Carlos; Torielli, Luca; Serapian, Stefano A.; Marchetti, Filippo; D'Acerno, Giovanni; Pirota, Valentina; Castelli, Matteo; Moroni, Elisabetta; Ferraro, Mariarosaria; Quadrelli, Paolo; Rasola, Andrea; et al.
Graphical abstract: Highlights: Atomistic Characterization of Long-range Allosteric Modulation in TRAP1. Isoform-selective inhibition of an Hsp90 family member. Dynamics-Driven Design of Improved Allosteric Modulators. Experimental Validation in Functional Assays and Tumor Models. Abstract: Herein we examine the determinants of the allosteric inhibition of the mitochondrial chaperone TRAP1 by a small molecule ligand. The knowledge generated is harnessed into the design of novel derivatives with interesting biological properties. TRAP1 is a member of the Hsp90 family of proteins, which work through sequential steps of ATP processing coupled to client-protein remodeling. Isoform selective inhibition of TRAP1 can provide novel information on the biomolecular mechanisms of molecular chaperones, as well as new insights into the development of small molecules with therapeutic potential. Our analysis of the interactions between an active first-generation allosteric ligand and TRAP1 shows how the small molecule induces long-range perturbations that influence the attainment of reactive poses in the active site. At the same time, the dynamic adaptation of the allosteric binding pocket to the presence of the first-generation compound sets the stage for the design of a set of second-generation ligands: the characterization of the formation/disappearance of pockets around the allosteric site that is used to guide optimize the ligands' fit for the allosteric site and improve inhibitory activities. The effects of the newly designed molecules are validated experimentally in vitro and in vivo . We discuss the implications of our approach as a promising strategy towards understanding the molecular determinants of allosteric regulation in chemical and molecular biology, and towards speeding up the design of allosteric small molecule modulators.